The Impact of Social Media on Investment Decision-Making: An Analytical Study - Shah, Meet; Patel, Raj; Sharma, Ansh; Chauhan, Rahul; Maseleno, Andino; Isnanto, R. Rizal (Greenation Research & Yayasan Global Resarch National, 2024)
This study investigates the influence of social media on investment decision-making, focusing on various factors such as frequency of use, preferred platforms, and perceptions of reliability. Using ANOVA analysis, the research reveals that the frequency of social media use and the belief in its reliability significantly affect investors' behaviours. Participants who use social media more frequently and trust the information sourced from it are more likely to let it guide their investment choices. However, the specific platforms and the overall belief in social media’s positive influence do not significantly affect decision-making. These findings underscore the complex role of social media in shaping investment behaviours, highlighting both its potential benefits and risks, such as the spread of misinformation. Future research could explore the credibility of different content types and the evolving landscape of social media's impact on global investment practices.